2012
DOI: 10.1007/s10764-012-9602-7
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Diet of an Extinct Hominin Taxon: The Role of Extant Primate Models

Abstract: Modern humans represent the only surviving species of an otherwise extinct clade of primates, the hominins. As the closest living relatives to extinct hominins, extant primates are an important source of comparative information for the reconstruction of the diets of extinct hominins. Methods such as comparative and functional morphology, finite element analysis, dental wear, dental topographic analysis, and stable isotope biogeochemistry must be validated and tested within extant populations before they can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 107 publications
0
43
0
Order By: Relevance
“…Some of the methods focus on the functional morphology of the masticatory system, others focus on tooth wear (both macroscopic and microscopic), and yet others focus on the physicochemical signatures that an animal's diet leaves within its hard tissues (1,2). Chemical methods include the use of strontium/calcium and barium/calcium ratios (3,4), but this study focuses on the analysis of stable isotopes of carbon (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Some of the methods focus on the functional morphology of the masticatory system, others focus on tooth wear (both macroscopic and microscopic), and yet others focus on the physicochemical signatures that an animal's diet leaves within its hard tissues (1,2). Chemical methods include the use of strontium/calcium and barium/calcium ratios (3,4), but this study focuses on the analysis of stable isotopes of carbon (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Wood and Schroer (2012) recently argued that because most extant primates eat varied diets, extinct primates, including P. boisei, should have been no different. However, neither the specific plant parts nor the species identities of dietary items can be inferred at present from stable isotope analysis, making it impossible to determine the dietary breadth of the putatively graminoid-eating extinct primates, T. oswaldi and P. boisei (Sponheimer et al, 2007;Cerling et al, 2011Cerling et al, , 2013.…”
Section: Implications For Understanding Theropith and Hominin Dietarymentioning
confidence: 99%
“…Some have suggested that P. boisei relied mostly on sedge corms year-round (Dominy, 2012;Macho, 2014), while others envision a more varied (gelada-like) diet of above-and belowground grass and sedge items, possibly coupled with opportunistic consumption of invertebrates, bird eggs, and small reptiles and mammals (Cerling et al, 2011;Grine et al, 2012;Wood and Schroer, 2012). Unlike T. gelada and T. oswaldi which both possessed specialized hands for digging (Jolly, 1970;Dunbar, 1983), P. boisei may have required tools to access underground food items to have consumed them in large quantities (Sponheimer et al, 2013b).…”
Section: Implications For Understanding Theropith and Hominin Dietarymentioning
confidence: 99%
“…We are occasionally reminded (e.g., Wood and Schroer, 2012) that inferences about the fossil record must be validated using extant primate models and, in a number of instances, the analogy of thick-enameled grey-cheeked mangabeys consuming hard objects only during selectively critical fallback periods has served that purpose (Scott et al, 2005;Sponheimer, 2013;Ungar and Sponheimer, 2011;Wood and Schroer, 2012). But just as there are multiple mangabeys, so too are there multiple analogies.…”
Section: Mangabeys and Homininsmentioning
confidence: 99%